Penambahan Register pada Form Login Aplikasi Master Data KBM dengan Metode Kriptografi AES - Sri Mulyati; Asep Sucipto Indra Sukma; Dwi Nur Febrianto; Fathul Ghina; Juhaendi Juhaendi; Endar Nirmala (Teknik Informatika Universitas Pamulang, 2022)
Incorrectly designed login forms can result in malicious credentials being exploited to gain unauthorized access. Designing the appearance of the form is enough to have a role so as not to make the user confused when faced with the login form page. In order to make it easier for users to access certain pages, the user must register first. Register also means the registration process (in the register) or system, with the display of the register on the login form, it will make it easier for users to register individually so that they can enter the application. Because previously the KBM master data login form application did not have a register, the author added a register form on the KBM master data application login form page, and needed to add another label that served as a link to the member registration menu that we had created. To do so, click the Standard tab > Labels (StdCtrls), then change the text on the Properties tab. B.